(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, some corrected Euler-Maclaurin-type inequalities are established by using various function classes involving Riemann-Liouville fractional integrals. We then present our findings using examples and special cases of the theorems that we have discovered. Moreover, we provide several fractional corrected Euler-Maclaurin-type for bounded functions. Additionally, for Lipschitzian functions, we create a few fractional corrected Euler-Maclaurin-type inequalities. Lastly, we provide some fractional corrected Euler-Maclaurin-type inequalities for functions of bounded variation.